A new species of planthopper in the genus Haplaxius (Hemiptera: Auchenorrhyncha: Fulgoroidea: Cixiidae) on palms in Costa Rica and a new country record for Haplaxius skarphion - Bahder, Brian W.; Barrantes, Edwin A. Barrantes; Echavarria, Marco. A. Zumbado; Mou, De-Fen; Helmick, Ericka E.; Bartlett, Charles R. (Zootaxa, 2020)
The genus Haplaxius is a large taxon of cixiid planthoppers that is of economic importance due to the ability of Haplaxius crudus to transmit lethal yellowing in coconut palms. Haplaxius dougwalshi sp. n. is established as a new taxon of Cixiidae in the tribe Oecleini collected from native palms in lowland tropical rainforest in Costa Rica. Placement in the genus Haplaxius is supported both by molecular evidence based on the COI and 18S genes as well as by morphological characters. This novel taxon was discovered during survey work in Costa Rica to look for phytoplasmas and document planthopper diversity on palms. Furthermore, Haplaxius skarphion was also collected from coconut palms during survey work and is reported for the first time in Costa Rica.